Clean and Efficient Synthesis of Graphene Nanosheets and Rectangular Aligned-Carbon Nanotubes Bundles Using Green Botanical Hydrocarbon Precursor: Sesame Oil - Kumar R.; Singh R.K.; Kumar P.; Dubey P.K.; Tiwari R.S.; Srivastava O.N. (My University, 2025)
A facile and rapid approach was used for the clean and efficient synthesis of graphene nanosheets (GNSs) and rectangular aligned carbon nanotubes (RA-CNTs) bundles. These structures were formed at different hot zones of the furnace. The sesame oil, a green natural precursor is used first time as a hydrocarbon precursor for the synthesis of GNSs and well packed RA-CNTs bundles. GNSs and RA-CNTs bundles were synthesized by spray pyrolysis of sesame oil with ferrocene as a catalyst, inside silica tube at 800 °C. This new precursor is appropriate for the synthesis of high quality and clean GNSs and RA-CNTs bundles. GNSs show the formation of few layers graphene which contains 6-8 graphene layers. FTIR spectra confirm that there is no more functional group attached on the surface of as synthesized materials. Growth of these nanostructures strongly depends on the temperature inside the tube. Raman studies show intense 2D peak as compared to G peak, signifying presence of GNSs. The investigations reveal that these novel carbon nanostructures synthesized by sesame oil are clean from carbonaceous impurities. © 2014 by American Scientific Publishers.